LEKER SI KOAL berbasis STEM Education untuk Mengukur Kemampuan Penalaran Matematis - Fiqhiya Hasnal Mala; Tri Novita Irawati; Sholahudin Al Ayubi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to develop LEKER SI KOAL (Lembar Kerja Siswa Konteks Aljabar) based on STEM Education as a learning media for measuring mathematical reasoning abilities. The research was conducted at MTs Ma'arif Ambulu involving 32 class VII students. Data was collected through questionnaires, tests, observations, interviews, and documentation, and the model of development research that was used is ADDIE which consisted of five stages: analysis, design, development, implementation, and evaluation. The results of the development of LEKER SI KOAL show that this learning media is included in the "decent" category with a percentage of 76%. Based on that the student responses via a questionnaire showed a percentage of 81%. Therefore, LEKER SI KOAL with STEM education approach “decent” to be developed as a learning medium.  Keywords: LEKER SI KOAL, STEM education, mathematical reasoning